Pembelajaran Interaktif Konsep Barisan Konvergen Bagi Mahasiswa - Lalu Sucipto (Beta: Jurnal Tadris Matematika, 2014)
This research aims at generating the interactivity learning procedure for convergent sequences concept for university students in the fourth semester at Offering C, mathematics education department, Malang Kanjuruhan University batch 2008/2009. Interactivity learning has several characteristics, namely intervention, collaboration, negotiation, and evaluation. In intervention, students are given problems related to convergent sequences concept whereas the lecturer provides intervention and problems. In negotiation, students discuss findings, while the lecturer plays a role as a mediator in the discussion. Next, in collaboration students sitting on the same bench cooperate to solve the problems; besides collaborating, they also negotiate and evaluate the result of negotiation. Then, in evaluation the lecturer evaluates the process and result of learning. Based on findings, it is found that interactivity learning for convergent sequences concept for university students in the fourth semester at Offering C, mathematics education department, Malang Kanjuruhan University is able to build a mathematic analysis. The interactivity learning procedures consist of 10 stages, namely (1) giving orientation about learning, (2) delivering the objective of learning, (3) motivating and percepting, (4) conducting intervention by the lecturer, (5) negotiating between the lecturer and students, (6) collaborating among students, (7) negotiating among students, (8) conducting intervention by the lecturer during students conducting collaboration and negotiation, (9) negotiating between the lecturer and students in order to draw a conclusion, and (10) evaluating by the lecturer.